Active Flow Control: Recent Advances in Fundamentals and Applications - Tang, Hui; Wen, Xin (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Active flow control (AFC) utilizes local active perturbations to induce changes in global flow behavior that result in aero/hydrodynamic performance improvement. It has been a vibrant research area with potential applications in a wide range of engineering fields. This Special Issue is a collection of 11 excellent research papers published in Actuators, showcasing and discussing new advances in both fundamental and applied AFC technologies.